2010 Florida Land Value Survey: Farmland Prices Still Down - Rodney L. Clouser; Charles Moss; Ronald Muraro; Laila Racevskis; Robert A. Morris (EDIS, 2011)
The Florida Farmland Value Survey, conducted by the Food and Resource Economics Department, University of Florida, provides estimates of the value of different types of agricultural land for geographic regions of the state. The most recent survey was conducted in November–December 2010 for land values in May 2010. It is apparent from the survey responses that the recessionary U.S. and Florida economies, the slower rate of Florida’s population growth, and the decline in the Florida housing construction industry continue to be reflected in a further decline in most Florida farmland values. Other factors such as rising energy related costs, additional costs for disease control for some commodities, and returns to farmland statewide also help explain the decline in the 2010 farmland values. For details, check out this 8-page fact sheet was written by Rodney L. Clouser, Charles Moss, Ronald Muraro, Laila Racevskis, and Robert A. Morris, and published by the UF Department of Food and Resource Economics, April 2011.